2020
DOI: 10.3390/su12072853
|View full text |Cite
|
Sign up to set email alerts
|

Alliances of Change Pushing Organizational Transformation Towards Sustainability across 13 Universities

Abstract: Universities are expected to play a leading role in developing and maintaining sustainability. To contribute to a systemic and dynamic understanding of organizational change that is necessary in order to play such a role, we comparatively analyzed processes of organizational changes towards sustainability across thirteen universities in Austria. This comparative analysis is based on data from guided interviews and document analysis and on validation of preliminary results via group discussion and individual co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 46 publications
(86 reference statements)
1
14
0
Order By: Relevance
“…Conclusions of the study by Bohunovsky et al [27] on pushing organizational transformation towards sustainability across 13 Universities in Austria are enriching for other HEIs, respecting the internal and external characteristics of each one. First and foremost, and prior to any changing process in HEIs towards sustainable development, it is important to bear in mind that organizational change processes towards sustainable development in these institutions are complex and experience numerous parallel developments, and have a wide range of institutional actors involved in this process, who may react differently to change.…”
Section: Digital Sustainable Development In Higher Educationmentioning
confidence: 91%
See 2 more Smart Citations
“…Conclusions of the study by Bohunovsky et al [27] on pushing organizational transformation towards sustainability across 13 Universities in Austria are enriching for other HEIs, respecting the internal and external characteristics of each one. First and foremost, and prior to any changing process in HEIs towards sustainable development, it is important to bear in mind that organizational change processes towards sustainable development in these institutions are complex and experience numerous parallel developments, and have a wide range of institutional actors involved in this process, who may react differently to change.…”
Section: Digital Sustainable Development In Higher Educationmentioning
confidence: 91%
“…Higher education is paramount in the promotion of sustainability at the environmental, economic and social levels [27][28][29]. Building on Kuzma, Doliveira, and Silva [30], Table 3 depicts the main competences for sustainability, as well as the definition and characteristics of each one of them.…”
Section: Digital Sustainable Development In Higher Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Only four papers highlighted how context factors can impact organizational change. For instance, Farinha et al [49] found that sectoral initiatives like the UN Decade of Education for Sustainable Development had limited effect on Portuguese HEIs, whereas Bohunovsky et al [50] claimed that a national university network acted like a major driver of change, particularly for HEIs starting their journey towards sustainability. Similarly, Lambrechts et al [51] report positive impacts from professional development initiatives driven by the government to facilitate the incorporation of sustainability into competence-based education.…”
Section: Contextmentioning
confidence: 99%
“…Overall, 14 papers (42.2% of total) contained at least one database entry constituting a leadership factor, and out of those, the majority contrasted different approaches of change leadership and their impact on organizational change (e.g., [50]) (see Figure 3). Most of these papers attach leadership to specific stakeholders and the degree of authority they wield.…”
Section: Leadershipmentioning
confidence: 99%